1984
DOI: 10.1111/j.1532-5415.1984.tb02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on the Clinical Significance of Fever in Ambulatory Adult Patients

Abstract: To study the effect of age on ultimate outcome of febrile illness, the authors prospectively studied 1,202 adult patients who came to an emergency room/walk-in clinic setting with temperatures of 101.0 degrees F (38.3 degrees C) or more. The patients were divided into four age categories: 17 to 40 years, 40 to 59 years, 60 to 79 years, and 80 years old or older. Advancing age was significantly (P less than 0.0005) associated with more serious disease, a higher rate of bacterial pathogen isolation, and a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 1 publication
(1 reference statement)
1
20
0
1
Order By: Relevance
“…Although the presence of fever may often indicate significant infection, its absence may not reliably exclude serious illness (28,29). In this study, abnormal temperature was significantly correlated only with prolonged duration of i.v.…”
Section: Discussionmentioning
confidence: 95%
“…Although the presence of fever may often indicate significant infection, its absence may not reliably exclude serious illness (28,29). In this study, abnormal temperature was significantly correlated only with prolonged duration of i.v.…”
Section: Discussionmentioning
confidence: 95%
“…34 It is important to recognize that a robust fever of 38.3°C or higher in a geriatric patient is indicative of a serious infection and needs to be promptly addressed. 40 …”
Section: Clinical Factors Influencing Infection Risk and Presentatmentioning
confidence: 99%
“…In older persons, a robust febrile response to infection has special significance. One large study of 11200 ambulatory patients demonstrated that an oral temperature of 38.3ЊC in elderly patients was usually due to a serious bacterial or viral infection [36]. Fever or at least an elevation of temperature over baseline will still occur in most cases of infection in the geriatric patient.…”
mentioning
confidence: 99%
“…Fever or at least an elevation of temperature over baseline will still occur in most cases of infection in the geriatric patient. However, unlike in the young, whose fevers are associated mostly with benign viral infections, in the elderly (especially those aged 180 years), oral temperatures reaching or exceeding 38.3ЊC will more likely be associated with serious bacterial or viral infections [36][37][38]. This can be expected to be particularly true for frail, debilitated patients.…”
mentioning
confidence: 99%